Peningkatan UMKM melalui Pendampingan dalam Mendapatkan Nomor Induk Berusaha (NIB) dan Sertifikasi Halal Produk - Riza Purnama; Teguh Anggoro; Tina Cahya Mulyatin; Dian Hadiani; Dara Siti Nurjanah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This Community Partnership Program (PKM) was designed to address the challenges faced by micro, small, and medium enterprises (MSMEs) in obtaining business legality and halal certification. Legal business status through the Business Identification Number (NIB) and halal certification are crucial for improving access to financing, expanding market opportunities, and enhancing consumer trust in products. The program implemented a comprehensive approach combining socialization, interactive training, and practical technical assistance to guide participants through the processes of NIB registration and halal certification applications. As a result, most participants successfully obtained their NIBs and gained a clear understanding of the steps required for halal certification. Beyond procedural knowledge, participants also realized that legal recognition and certification serve as strategic foundations for strengthening and upgrading their businesses. Tangible impacts observed include increased product competitiveness, better access to government support schemes, and opportunities for collaboration with other businesses. Overall, the program demonstrates that targeted guidance and capacity-building activities can effectively enhance the legitimacy, marketability, and sustainability of MSMEs, empowering entrepreneurs to grow their businesses confidently while meeting regulatory and consumer standards.